Solid Waste Engineering and Management Volume 3 - Wang, Lawrence K.; Wang, Mu-Hao Sung.; Hung, Yung-Tse.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is the third volume in a three-volume set on Solid Waste Engineering and Management. It focuses on tourism industry waste, rubber tire recycling, electrical and electronic wastes, health-care waste, landfill leachate, bioreactor landfill, energy recovery, innovative composting, biodrying, and health and safety considerations pertaining to solid waste management.. The volumes comprehensively discuss various contemporary issues associated with solid waste pollution management, impacts on the environmental and vulnerable human populations, and solutions to these problems.
Chapter 1-Solid waste management in the tourism industry -- Chapter 2-Rubber recycling and disposal -- Chapter 3-Electronic and electrical waste disposal -- Chapter 4-Clinical waste management -- Chapter 5-Energy Recovery from waste -- Chapter 6-Dredging operation, management and disposal for environment restoration -- Chapter 7-Biodrying in Solid Waste Treatment -- Chapter 8-Management and disposal of radioactive wastes -- Chapter 9-Landfill leachate treatment -- Chapter 10-Health and safety considerations in waste management.
Keywords: Environment; Refuse and refuse disposal; Environmental engineering; Biotechnology; Bioremediation; Environmental Sciences; Waste Management/Waste Technology; Environmental Engineering/Biotechnology.; Refuse and refuse disposal